(untitled) (Research, Society and Development, 2020)
Introduction: Chronic kidney disease is characterized by the presence of inflammatory processes that contribute to homeostatic, physiological and functional changes. These conditions are mainly due to the decrease in antioxidant capacity, either due to the very common deficiency of selenium, or its loss through dialysis processes, which suggests that supplementation of this mineral may be beneficial for these patients. Objective: To investigate in the literature the effects of selenium supplementation on antioxidant activity in chronic renal patients. Methods: This is an integrative literature review, carried out by searching for original articles, in Portuguese, English and Spanish, indexed in the Pubmed and Lilacs databases. Results: Of the 108 articles, 5.5% (n=6) were included in this review, for full reading of the text. It was observed that 50% (n=3) of the studies demonstrated that selenium supplementation increased the activity of the enzyme GSH-Px. Another half (50%, n=3) of the articles, observed that a higher concentration of Se in the plasma of patients aged 12 to 80 years, reduced serum MDA levels. And only 16.6% (n=1) pointed to a significant increase in the activity of NK cells. Conclusion: Se supplementation was shown to be effective in improving the antioxidant defense of chronic renal patients.